2018
DOI: 10.1007/s10753-018-0736-4
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1/CX3CR1 Axis Contributes to Angiotensin II-Induced Vascular Smooth Muscle Cell Proliferation and Inflammatory Cytokine Production

Abstract: Angiotensin II (Ang II) dysregulation has been determined in many diseases. The CX3CL1/CX3CR1 axis, which has a key role in cardiovascular diseases, is involved in the proliferation and inflammatory cytokine production of vascular smooth muscle cells (VSMCs). In this study, we aim to explore whether Ang II has a role in the expression of CX3CL1/CX3CR1, thus contributing to the proliferation and pro-inflammatory status of VSMCs. Cultured mouse aortic VSMCs were stimulated with 100 nmol/L of Ang II, and the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…All six genes have previously been reported in the context of radiation or DNA damage response and fall into three main biological roles: cell cycle arrest, hemoglobin metabolism, and inflammatory response (Table 1 ). The prior relevant literature on Cdkn1a [ 53 , 54 ], Gdf15 [ 55 , 56 ], Ckap2 [ 57 , 58 ], Alas2 [ 59 , 60 ], Aplnr [ 61 , 62 ] and Cx3cr1 [ 63 , 64 ] are listed in Table 1 . We validated the expression of the most significantly upregulated and downregulated mRNAs in our data using RT-qPCR (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…All six genes have previously been reported in the context of radiation or DNA damage response and fall into three main biological roles: cell cycle arrest, hemoglobin metabolism, and inflammatory response (Table 1 ). The prior relevant literature on Cdkn1a [ 53 , 54 ], Gdf15 [ 55 , 56 ], Ckap2 [ 57 , 58 ], Alas2 [ 59 , 60 ], Aplnr [ 61 , 62 ] and Cx3cr1 [ 63 , 64 ] are listed in Table 1 . We validated the expression of the most significantly upregulated and downregulated mRNAs in our data using RT-qPCR (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…These inflammatory cells in the intima were directly correlated with the number of CXCR1 + cells, most of which were VSMCs [30]. In addition, angiotensin II (Ang II) dysregulation was determined in many cardiovascular diseases, and it could upregulate CX3CR1 expression in VSMCs via the NADPH oxidase/ROS/p38 MAPK pathway [31]. Interestingly, CX3CL1 + and CX3CR1 + cells are also present in AAAs, indicating their contributions to the recruitment of inflammatory cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ang II is widely used to induce hypertension and vascular remodeling as an animal model of hypertension [2426]. It is well known that Ang II induces VSMC proliferation [27], which is widely used as a model of VSMC proliferation in vitro [2830]. We found that BCL6 overexpression attenuated while BCL6 knockdown enhanced the Ang II-induced VSMC proliferation, indicating that BCL6 is an important protective factor in inhibiting Ang II-induced VSMC proliferation.…”
Section: Discussionmentioning
confidence: 99%